Few-layer graphitic shells networked by low temperature pyrolysis of zeolitic imidazolate frameworks. (22nd January 2018) - Chen, Yinxiang; Zhang, Wei; Jiang, Xiangfen; Kaneti, Yusuf Valentino; Tang, Daiming; Wang, Xuebin; Alshehri, Abdulmohsen Ali; You, Jungmok; Yamauchi, Yusuke; Hu, Ming
Abstract : Low-temperature solid-state pyrolysis of ZIF-67 weaves graphitic shells into capsules. Abstract : Few-layer graphitic shell networks show great promise in energy storage applications such as electrochemical accommodation of alkaline ions. However, the networking and graphitization processes remain a challenge because of the complicated procedures and high temperature used for fabrication. In this work, we report a simple synthetic method by employing low-temperature solid-state pyrolysis of ZIF-67 crystals to weave graphitic shells consisting of 3–10 layers into capsules. Owing to their unique structure, the few-layer graphitic shell networks show excellent electrochemical performance for fast sodium ion storage.